2021
DOI: 10.1590/1678-4685-gmb-2020-0349
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol prevents inflammation and oxidative stress response in LPS-induced human gingival fibroblasts by targeting the PI3K/AKT and Wnt/β-catenin signaling pathways

Abstract: This study aimed to elucidate the anti-inflammatory and antioxidant properties of resveratrol (RSV) in human gingival fibroblasts (HGFs) following stimulation by P. gingivalis lipopolysaccharide (LPS). The levels of the inflammatory cytokines IL-1β, IL-6, IL-8 and TNFα, the activity of the antioxidant enzymes SOD and GSH-Px, and the levels of MDA, were evaluated by ELISA. It was observed that the expression of IL-1β, IL-6, IL-8 and TNFα in LPS-induced HGFs was significantly downregulated by RSV in a dose-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…1 ). Studies have demonstrated that AGEs-induced oxidative stress leads to chronic inflammation 27 , 28 and RES has anti-oxidant activity, 24 thus we utilize DCFH-DA to investigate the formation of ROS. Results showed that AGEs significantly increased the production of ROS and administration of RES significantly suppressed ROS production ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). Studies have demonstrated that AGEs-induced oxidative stress leads to chronic inflammation 27 , 28 and RES has anti-oxidant activity, 24 thus we utilize DCFH-DA to investigate the formation of ROS. Results showed that AGEs significantly increased the production of ROS and administration of RES significantly suppressed ROS production ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“… 23 Resveratrol has also been shown to diminish inflammation and oxidative stress by inhibiting PI3K/Akt and WNT/β-catenin signaling pathway in LPS-induced HGFs. 24 Therefore, we further investigated whether resveratrol has the potential to decrease AGEs-mediated senescence in gingival fibroblasts. This study aimed to explore the effect and molecular mechanisms of resveratrol on AGEs-induced inflammaging in HGFs.…”
Section: Introductionmentioning
confidence: 99%
“…This study started from the evidence that RSV exerts beneficial effects on different cell types that are involved in the oral wound healing process. However, its limited bioavailability restricts its use as a pharmacological agent [ 29 , 30 , 31 ]. These limits drove us to synthetize sulfonamide RSV derivatives 1a – j [ 12 , 22 ] and to investigate their effects on human cells to verify their ability to improve and promote the cellular activities of HUVECs, HGFs, and HOBs.…”
Section: Discussionmentioning
confidence: 99%
“…It may be partly because resveratrol can act on various targets. Regarding the anti-inflammatory effects of resveratrol ( Baur and Sindair, 2006 ), the PI3K pathway ( Li et al, 2021 ), and the SIRT1/NRF2 signaling pathway ( Nie et al, 2020 ) are also involved. It was previously reported that SIRT1 activation inhibited ROS-associated NLRP3 inflammasome activation and ameliorates cardiac pyroptosis during myocardial I/R injury through Akt-PDH signaling pathway ( Han Y et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%